2014
DOI: 10.3389/fcell.2014.00063
|View full text |Cite
|
Sign up to set email alerts
|

Common themes in PrP signaling: the Src remains the same

Abstract: The ability of the cellular prion protein (PrPC) to trigger intracellular signals appears central to neurodegeneration pathways, yet the physiological significance of such signals is rather puzzling. For instance, PrPC deregulation disrupts phenomena as diverse as synaptic transmission in mammals and cell adhesion in zebrafish. Although unrelated, the key proteins in these events -the NMDA receptor (NMDAR) and E-cadherin, respectively- are similarly modulated by the Src family kinase (SFK) Fyn. These observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…S4B). This discrepancy is likely attributed to the conformational state of affecting oAb and the type of PrP c coreceptor, but further delineations are certainly needed (43,44). In addition, the prolonged activation of LYN may potentiate oAb 1-42 -triggered neurotoxicity combined with enhanced expression of FcgRIIb, considering that the expression and phosphorylation of FcgRIIb2 are induced by oAb for .24 h in neuronal cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…S4B). This discrepancy is likely attributed to the conformational state of affecting oAb and the type of PrP c coreceptor, but further delineations are certainly needed (43,44). In addition, the prolonged activation of LYN may potentiate oAb 1-42 -triggered neurotoxicity combined with enhanced expression of FcgRIIb, considering that the expression and phosphorylation of FcgRIIb2 are induced by oAb for .24 h in neuronal cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, ablation of Fyn function has ameliorated AD phenotype . The suggested pathological signaling cascade via SFKs is summarized in Figure , where the extracellular binding domain of Aβo activates the gatekeeper PrPC and Fyn plays a crucial role in this cascade …”
Section: Future Directions For Alzheimer's Disease Treatmentmentioning
confidence: 99%
“…159 The suggested pathological signaling cascade via SFKs is summarized in Figure 12, where the extracellular binding domain of Aβo activates the gatekeeper PrPC and Fyn plays a crucial role in this cascade. 160 Moreover, Fyn has been uniquely linked to the two major pathological hallmarks of AD, because it is not only activating by Aβ via PrPC, but also it interacts with tau. 155 It has been reported that Fyn is involved in Tau phosphorylation, which results in synapse damage, behavioral deficits and electroencephalographic deformities in APP transgenic mice.…”
Section: Fyn Kinase Inhibitionmentioning
confidence: 99%
“…Uncovering mechanisms of PrP function in vivo remains a challenging task because no overt phenotypes are evident in PrP knockout mice, save for subtle abnormalities in olfactory physiology, neurogenesis, peripheral myelination and muscle regeneration [ 9 13 ]. Unfortunately, the biochemical basis of these defects and their connection to prion disease are yet to be established.…”
Section: Introductionmentioning
confidence: 99%